(untitled) (Journal of the College of Basic Education, 2022)
Psychologists believe that the beauty of an object is what satisfies our aesthetic sense, and its satisfaction is achieved by tasting or appreciating the unity of harmony inherent in the heritage, and giving value to the aesthetic relations between our sensory perceptions and tasting through appreciation, as appreciation is the state of the thing.As for tasting, it is a state of enjoyment under feeling that is predominantly emotional. It suffices in tasting that tacit interaction between the beautiful thing and the one who enjoys it.As for the ancient inhabitants of the Mesopotamia Valley, the information available about them confirms that they do not have specialized jurisprudence on the subject of beauty. However, we can say that their beliefs regarding beauty and beautiful phenomena did not depart from things that serve human life and life in general.